Myeloperoxidase influences the complement regulatory function of modified C-reactive protein. Issue 4 (May 2014) - Xu, Peng-cheng; Li, Zhi-ying; Yang, Xiao-wei; Zhao, Ming-hui; Chen, Min
In patients with active anti-neutrophil cytoplasmic Ab (ANCA)-associated vasculitis (AAV), there are high levels of circulating C-reactive protein (CRP), which can inhibit the alternative complement pathway by binding factor H and triggering the classical complement pathway by binding C1q. However, the alternative, not the classical, complement pathway has been proven to play an important role in AAV. We found that both purified myeloperoxidase (MPO) and MPO released from ANCA-stimulated neutrophils could bind modified CRP (mCRP), but not pentameric CRP. Furthermore, MPO could block the binding between mCRP and factor H, as well as the binding between mCRP and C1q. Binding with mCRP did not influence the enzymatic activity of MPO. Binding with mCRP also did not influence the binding between MPO and its physical inhibitor, ceruloplasmin, as well as the binding between MPO and MPO–ANCA. The results indicated that MPO might be a complement regulator and inhibit the negative regulatory effect of CRP on the alternative complement pathway.